Developments and recent advancements in the field of endogenous amino acid selective bond forming reactions for bioconjugation. (22nd May 2015) - Koniev, Oleksandr; Wagner, Alain
Abstract : Recent advances in bond-forming bioconjugation reactions of native amino acid residues with emphasis on the most practically relevant methodologies. Abstract : Bioconjugation methodologies have proven to play a central enabling role in the recent development of biotherapeutics and chemical biology approaches. Recent endeavours in these fields shed light on unprecedented chemical challenges to attain bioselectivity, biocompatibility, and biostability required by modern applications. In this review the current developments in various techniques of selective bond forming reactions of proteins and peptides were highlighted. The utility of each endogenous amino acid-selective conjugation methodology in the fields of biology and protein science has been surveyed with emphasis on the most relevant among reported transformations; selectivity and practical use have been discussed.